Underdevelopment in Rural Romania: Land Ownership and Agriculture from 1918 to 2018 - Țâra, Sergiu (Calitatea Vieții, 2018)
Land ownership has been one of the most important elements of wealth in the entire evolution of humankind. In Romania, during the last one and a half century, land ownership has had an important evolution, given at least four major agricultural laws, each of them attempting to solve for good what has come to be known as “the agrarian issue”. The article is a comparative analysis of the main provisions thereof, and of their impact on Romanian society. The reached conclusion is that agricultural holdings in Romania used to, and continue to, be fragmented, mostly dwarf in size, economically inefficient, lacking a modern set of agricultural tools and machinery put in place, with low quantitative and qualitative productions as a result. The causes of these state of facts are most diverse and differ in time: the overpopulation of the rural area, the absence of an industrial and tertiary sector developed enough to absorb the population excess in agriculture, the low level of education of the rural population, economic inefficiency, the lack of a coherent political vision, etc. All this has caused the Romanian rural population to live on the brink of poverty and the agricultural sector to continue to be underdeveloped.